Mineral Prospect Identification Using Inducedpolarization And Very Low Frequency-EM Methods At Sangon, Kalirejo Village, Kokap Sub-District, Kulonprogo Regency, Special Region Of Yogyakarta, Indonesia - Adera Nurul; Arga Kunang; Arief Khoiruddin; arif fikri; Benedicta Nathania; Dobrak Tirani; Enrico Diofano; Haryo Satrio; Hesti Nilamhapsari; Ihsan Median; Indah Sasmita; Ivona Annisa; Jum Satriani; Laila A; Mariana Kambey; M Syahdan; Oktavianus Eko; Rahmat Hidayat; Ramdhani Ramdhani; Satrio P; Siti Suci; Zeni A; Zukhruf Delva (Department of Physics Universitas Gadjah Mada, 2020)
A research of induced polarization and very low frequency method was carried out at Sangon Village, Kulonprogo to identify mineralization zone. The result of these methods were able to be used to support each other. Mineralization zone is shown by high resistivity and high hargeability area of induced polarization method, and is also shown by high electric current density area of very low frequency method. Interpretation of resistivity and chargeability model shows that mineralization zone is mostly located at the depth below 10 m from surface. On the other hand, interpretation of electric current density models at depth 10 m and 20 m show that mineralization zone is not well distributed respect to alteration zone, which is the character of low sulfidation epithermal type, mostly at north-south direction.